Achieving routine sub 30 minute door-to-balloon times in a high volume 24/7 primary angioplasty center with autonomous ambulance diagnosis and immediate catheter laboratory access. - Dalby, M; Kharbanda, R; Ghimire, G; Spiro, J; Moore, P; Roughton, M; Lane, R; Al-Obaidi, M; Teoh, M; Hutchison, E; Whitbread, M; Fountain, D; et al. (2009)
BACKGROUND: In primary angioplasty (primary percutaneous coronary intervention [PPCI]) for acute myocardial infarction, institutional logistical delays can increase door-to-balloon times, resulting in increased mortality. METHODS: We moved from a thrombolysis (TL) service to 24/7 PPCI for direct access and interhospital transfer in April 2004. Using autonomous ambulance diagnosis with open access to the myocardial infarction center catheter laboratory, we compared reperfusion times and clinical outcomes for the final 2 years of TL with the first 3 years of PPCI. RESULTS: Comparison was made between TL (2002-2004, n = 185) and PPCI (2004-2007, n = 704); all times are medians in minutes (interquartile range): for TL, symptom to needle 153 (85-225), call to needle 58 (49-73), first professional contact (FPC) to needle 47 (39-63), door to needle 18 (12-30) (mortality: 7.6% at 30 days, 9.2% at 1 year); for interhospital transfer PPCI (n = 227), symptom to balloon 226 (175-350), call to balloon 135 (117-188), FPC to balloon 121 (102-166), first door-to-balloon 100 (80-142) (mortality: 7.0% at 30 days, 12.3% at 1 year); for direct-access PPCI (n = 477), symptom to balloon 142 (101-238), call to balloon 79 (70-93), FPC to balloon 69 (59-82), door to balloon 20 (16-29) (mortality: 4.6% at 30 days, 8.6% at 1 year). There was no difference between direct-access PPCI and TL times for symptom to needle/balloon. Direct-access PPCI was significantly quicker for the group than in-hospital thrombolysis for door to needle/balloon times due to the lack of any long wait patients (P < .001). CONCLUSIONS: Interhospital transfer remains slow even with rapid institutional door-to-balloon times. With autonomous ambulance diagnosis and open access direct to the catheter laboratory, a median door-to-balloon time of <30 minutes day and night was achieved, and >95% of patients were reperfused within 1 hour.